Dynamic voltage restorer using sliding mode controller: Experimental studies - Toumi Toufik; Benabedellah Abdelkader; Abdelkhalek Othmane; Allali Ahmed; Benhamou Aissa; Hafsi Oussama (Institute of Advanced Engineering and Science, 2021)
The simulation and implementation of a sliding mode control strategy for a single-phase dynamic voltage restorer (DVR) to mitigate load voltage sag swell and harmonics is presented in this work. The control strategy's goal is to compensate for the required voltage by regulating the DVR's voltage via an injection transformer while keeping the load voltage constant. The ability of the DVR to achieve a good performance greatly depends on its control strategy. The controller used in this work is based on SMC theory, which consists of creating a passivation output and a storage function to use as a function of Lyapunov. The proposed control scheme of the DVR is initially evaluated in simulations using MATLAB and validated using a laboratory-scale prototype of the entire system, including a source, the DVR circuit and a load. The control scheme is implemented on a dSPACE 1104 board and the MATLAB real-time toolbox. Both the experimental results have demonstrated the effectiveness the proposed control strategy of DVR in mitigating power qualities issues and therefore enhancing the performance of the network.